An analysis of issues for the management of post-disaster housing reconstruction - Bilau, Abdulquadri Ade; Witt, Emlyn (International Journal of Strategic Property Management, 2016)
There is an urgent need to improve the management of housing reconstruction programmes. Post-disaster housing reconstruction represents a significant portion of global property investment but its management has often proved to be ineffective. Although the post-disaster context makes management more challenging, it also offers exceptional opportunities to invest in and develop a more resilient built environment. On the basis of a systematic review of the existing literature, characteristics of the housing reconstruction context and successes, failures and management issues arising from historical housing reconstruction programmes were identified. These were synthesized into a conceptual framework that relates the contextual characteristics with management strategies and with the desired outcomes for housing reconstruction initiatives. This framework will enable field data collection in order to better understand the interrelationships between context, management strategies and outcomes. Ultimately, it is intended to provide practitioners with decision support tools for selecting appropriate housing reconstruction management strategies.